Literature Learning in the Students of Class-X at SMA Muhammadiyah Pangkep - Roslina Roslina; Mutawakkil Mutawakkil; Nashruddin Nashruddin; Ahmad Amin (JELITA, 2020)
This research aims at decribing the process of literature learning at a senior high school in the academic year of 2019/2020. This study is a descriptive qualitative research with the subjects are a teacher of literature and 15 students of the tenth grade at SMA Muhammadiyah Pangkep. The instruments for collecting data are observation result, interview result, and documentation. The research results showed that the goals of literature learning were well-achieved, indicated by the students’ capability in appreciating literary works and expressing the appreciation in the form of poems and short stories. The success in learning literature was marked by the increase of the students’ reading interest, their frequently browsing of articles on both literary and non-literary materials from various websites, and their work products in the form of poetry. The achievement of those students was caused by the effort applied by the teacher, namely supporting students in developing their creativity on literary activities, either inside or outside school hours, such as short story writing contest, poetry writing contest, poetry reading contest, and drama performance.